Evolution of Dry Zone Afforestation in Madras State - Rajasingh, G. J. (Indian Forester, 1968)
Till recently our approach to forestry and its problems has been conservative, guided by traditional and time consuming methods involving little expense and modest returns. This in part was due to the poor industrial orientation of our forests at that time. Now we strive to produce the maximum timber or wood in the shortest possible time through plantations of pines, eucalypts and poplars aided by fertilizers, better strains, hybrids and machines. The series of changes undergone by forestry practices were part of a process of evolution. Nearly 70 per cent of the State forests come under dry zone located on level ground and low hills. Excessive cutting and grazing, low rainfall, long period of drought and hardened soil are the problems. Average yield per hectare is hardly 12 tonnes under a 40 year rotation. Earliest recorded afforestation dates back to 1848 of moving sands by private enterprise. Avenue trees were planted by British civil servants from 1862 and by 1890 some small plantations of forest trees were established within the dry zone. First attempts to improve the dry fuel forests began in 1904 in the form of enrichment sowings in blanks. The rapid destruction of forests under the control local bodies warned foresters about the need for greater conservation of state forests. In 1926 began the rab method of afforestation with emphasis on brushwood burn and weed control, borrowed from Bombay and teak planting centres. The finding that 11-10 per cent of the stools died by coppicing methods and that this loss was not being made up by seedling regeneration gave a fillip to afforestation. In 1940 the kumri method was adopted everywhere using the principle of weed control by burning and farming, also learnt from the teak planting centres. It continued till 1952 with ideas like direct sowings, brushwood burn and weed control reigning supreme. 1953 opens a new chapter. Belief in direct sowings, brushwood burn and taungya was discarded; attention turned to drought, low rainfall and hard soil. Emphasis was laid on moisture conservation methods; pet plants replaced direct sowing. But moisture conservation methods failed against competition from the tenacious bush. Experience elsewhere and advice by visiting experts gave farther impetus to afforestation. The advantages of Anacardium occidentale and Eucalyptus terelicornis as certain drought resistants and the keen dollar demand for the kernal of the former stimulated in 1956 extensive planting of the former and trials of the later. Results were disappointing, but accidental farming in 1961 in established plantations produced astonishing results and opened the era of thorough site preparation. There are today about 211,000 ha under A. occidentale. Extensive afforestation with E. tereticornis using polipots plants commenced in 1962; now machines are slowly coming into use for site preparation. Casuarina equisetifolia is being planted along the sea coast for the past 105 years in much the same way.